Governance and the Manufacturing Sector Growth among the BRICS Nations - Musiita , Benjamin; Turyareeba, Dickson; Mugambe, Kenneth; Wamala, Anthony; Jeke, Leward; Boyi, Ben (Journal of Economics and Behavioral Studies, 2023)
The objective of this study was to examine the relationship between selected governance factors and growth rates in the manufacturing sector’s output among the member states of BRICS. This study examined the institutionalized growth theory and explored four governance factors: government effectiveness, regulatory quality, control of corruption, and voice and accountability. The study also considered factors associated with both exogenous and endogenous growth theories. The estimation process involves applying the first difference generalized method of moments (D-GMM) on a linear dynamic panel model. The data spans from 2010 to 2021. The findings of this study suggest that among the BRICS nations, government effectiveness is the most significant predictor of growth in the manufacturing sector, out of the four governance factors that were examined. The factors of voice and accountability, control of corruption, and regulatory quality did not demonstrate the capacity to exert influence on variations in the growth of the manufacturing sector within the BRICS countries. Unlike prior studies, our research incorporates a range of established growth theories in constructing the empirical model. Additionally, we employ an instrumental variable approach for dynamic panel data analysis. We utilize robust standard errors to address potential issues of endogeneity and model misspecification. Therefore, BRICS countries should devote a sizeable portion of their resources to building solid mechanisms that make it easier for the implementation, oversight, and thorough reporting of government activities inside their manufacturing sector. This strategy could increase governmental effectiveness, which would encourage overall manufacturing sector growth.